2010
DOI: 10.1111/j.1440-1746.2010.06306.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of branched‐chain amino acid‐enriched nutrient for patients with hepatocellular carcinoma following radiofrequency ablation: A one‐year prospective trial

Abstract: Supplementation with BCAA-enriched nutrients for one year in cirrhotic patients with HCC after RFA therapy can perform safety and improve both nutritional state and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 28 publications
0
44
0
1
Order By: Relevance
“…The effect of BCAAs on HCC recurrence after radiofrequency ablation (RFA) remains unclear. Two prospective studies showed that BCAA supplementation improved nutritional state and liver function, but its effect on HCC recurrence was not determined [78,79] . However, a recent retrospective study showed that oral BCAA supplementation after RFA improved 1 year (61.8% vs 52.0%) and 3-year (28.0% vs 12.0%) progression-free survival rates compared with a control group after RFA (P = 0.013) [80] .…”
Section: Bcaas For Liver Cirrhosismentioning
confidence: 99%
“…The effect of BCAAs on HCC recurrence after radiofrequency ablation (RFA) remains unclear. Two prospective studies showed that BCAA supplementation improved nutritional state and liver function, but its effect on HCC recurrence was not determined [78,79] . However, a recent retrospective study showed that oral BCAA supplementation after RFA improved 1 year (61.8% vs 52.0%) and 3-year (28.0% vs 12.0%) progression-free survival rates compared with a control group after RFA (P = 0.013) [80] .…”
Section: Bcaas For Liver Cirrhosismentioning
confidence: 99%
“…In general, energy metabolism is evaluated according to the non-protein respiratory quotient (npRQ) based on indirect calorimetry (11)(12)(13). Moreover, recent studies have shown that supplementation with BCAA-enriched nutrients improves the npRQ in HCC patients after RFA (14). However, no studies have examined whether BCAA granule supplementation improves the npRQ in HCC patients after RFA.…”
Section: Introductionmentioning
confidence: 99%
“…In these patients with underlying PEM, RFA therapy may further worsen their nutritional condition and even occasionally lead to the development of ascites and jaundice, resulting in an irreversible outcome. [8][9][10] Supplementation with BCAA for the treatment of patients with liver disorder has been attracting attention. BCAA has a variety of pharmacological effects.…”
mentioning
confidence: 99%